Preparation method of high-strength composite bipolar plate
The preparation of porous carbon balls and airflow mixing technology through one-step hydrothermal method solves the problem of poor interface compatibility of composite bipolar plates, and achieves high-strength and high conductivity bipolar plate preparation, simplifies the process flow, and is suitable for industrial production.
Patent Information
- Application Number
- CN202411775095.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The existing composite bipolar plates have poor interfacial compatibility between carbon materials and resins, resulting in the formation of gaps/holes, affecting the safe and stable operation of the battery and mechanical strength. The existing modification methods are cumbersome and difficult to operate, which is not conducive to industrialization. Production.
Porous carbon balls are prepared by one-step hydrothermal method, and the airflow is used to improve the adsorption ability of porous carbon balls to polymer resin powder, enhance the interface compatibility, and mix fluoropolymers, porous carbon balls and carbon materials through the airflow, and mold them into Reduce gaps/holes and improve mechanical strength.
The preparation of high-strength composite bipolar plates is realized, the process flow is simplified, the conductivity and mechanical strength are improved, and the operation is reduced, making it suitable for industrial production.
Smart Images

Figure CN119252961A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical technology, and in particular to a method for preparing a high-strength composite bipolar plate. Background Art
[0002] Bipolar plates are one of the key materials for flow batteries and fuel cell stacks, and they play the role of collecting current and supporting electrodes. Carbon / polymer composite bipolar plates have both the good mechanical properties and processability of polymer resins and the excellent electrical conductivity of carbon materials, making them an alternative to metal bipolar plates and graphite bipolar plates.
[0003] Composite bipolar plates are usually made by mixing multiple carbon materials, adding resin as a binder, and using injection molding or compression molding to prepare them. Carbon materials can effectively improve the conductivity of bipolar plates, and resins can enhance the mechanical strength and air tightness of bipolar plates. However, due to the poor interfacial compatibility between carbon materials and resins, gaps / holes will appear at the interface during the blending process, which can easily cause gas / electrolyte penetration and affect the safe and stable operation of the battery. At the same time, continuous gaps or holes can easily form stress concentration points, affecting the mechanical strength of the bipolar plates.
[0004] To solve this problem, some work has focused on modifying carbon materials or resins. The Chinese patent document with publication number CN117325491A discloses a composite bipolar plate, a preparation method thereof, and a fuel cell. The graphite material is passed through nitrogen and hexamethyldisilazane vapor to react to obtain modified graphite. The resin and the modified graphite are mixed by a wet method to obtain a composite material. The composite material is pressed into shape and cured to obtain a composite bipolar plate. This method enhances the compatibility and bonding between graphite and resin by modifying the graphite material, thereby improving the mechanical strength and air tightness of the composite bipolar plate.
[0005] The Chinese patent document with publication number CN114976086A discloses a composite graphite bipolar plate for fuel cells and a preparation method thereof, wherein a thermosetting resin polymer is directly grafted with graphene to prepare modified graphene, and the modified graphene powder is hot-pressed to form a bipolar plate. The above method improves the interface compatibility between the carbon material and the resin by modifying the carbon material or the resin, reduces the formation of gaps / holes inside the bipolar plate, and enhances the mechanical strength of the bipolar plate. However, the above modification method has complicated steps and is difficult to operate, which increases the complexity of the bipolar plate manufacturing process and is not conducive to industrial production and application. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a high-strength composite bipolar plate. The method prepares porous carbon balls by a one-step hydrothermal method, uses airflow to improve the adsorption capacity of the porous carbon balls to polymer resin powder, enhances the interface compatibility between the polymer resin and the porous carbon balls, and further reduces the internal gaps / holes of the bipolar plate during the bipolar plate forming process, improves the mechanical strength of the bipolar plate, and realizes the preparation of a high-strength composite bipolar plate.
[0007] To achieve this object, the technical solution of the present invention is: A method for preparing a high-strength composite bipolar plate, the steps are as follows: 1) Mixing lignin, surfactant aqueous solution and alkaline aqueous solution, performing hydrothermal treatment to obtain a suspension, filtering, washing and drying the suspension to obtain porous carbon balls; (2) placing the fluorine-containing polymer, porous carbon balls and carbon material in an air flow mixer and mixing them by air flow to obtain a blend; (3) The blend is compression molded to produce a high-strength composite bipolar plate.
[0008] Preferably, in step (1), the surfactant is one of sodium dodecyl sulfate, sodium fatty alcohol polyoxyethylene ether sulfate or sodium secondary alkyl sulfonate; the mass fraction of the surfactant aqueous solution is 0.18% to 0.4%; the alkaline aqueous solution is one of sodium hydroxide and potassium hydroxide aqueous solutions; the mass fraction of the alkaline aqueous solution is 5% to 7%; the mass ratio of the lignin, the surfactant and the alkaline compound in the alkaline aqueous solution is 1:0.03 to 0.1:1 to 2.
[0009] Preferably, in step (1), the hydrothermal treatment temperature is 140-180° C., and the hydrothermal treatment time is 6-10 h.
[0010] Preferably, in step (2), the fluorine-containing polymer is one of ethylene-tetrafluoroethylene copolymer, polyvinylidene fluoride, or polyvinylidene fluoride-hexafluoropropylene copolymer; the particle size of the fluorine-containing polymer is 5 nanometers to 2 micrometers; the carbon material is one or a combination of flake graphite, carbon nanotubes, or carbon nanofibers; the mass ratio of the fluorine-containing polymer, porous carbon balls, and carbon material is 1:0.2-0.4:0.33-1.25. Compared with conventional thermoplastic polymers such as high-density polyethylene and polypropylene, the composite bipolar plate prepared with fluorine-containing polymer as raw material has higher conductivity, which is attributed to the higher polarity of fluorine-containing polymer, which can enhance the dispersion performance of carbon material in PVDF matrix, form a rich conductive network, and thus improve the conductivity of bipolar plate. Based on the large specific surface area and rich mesopore structure of porous carbon balls, the ability to adsorb or embed fluorine-containing polymer powder on the surface of porous carbon balls can be achieved during the blending process. During the molding process of the blend, the molten polymer will penetrate into the pores of the porous carbon balls, thereby improving the interfacial bonding strength of the composite material and reducing the internal porosity.
[0011] Preferably, in step (2), the air flow mixing pressure is 0.5-1 MPa, and the mixing time is 30-60 seconds. The surface of the porous carbon ball has a rich mesoporous structure. When the compressed air jet airflow is used to drive the blend to move, the rich pore structure on the surface of the porous carbon ball provides a large number of adsorption sites, which can improve the adsorption or embedding ability of the fluorine-containing polymer powder on the surface of the porous carbon ball. During the molding process of the blend, the molten polymer will penetrate into the pores of the porous carbon ball, thereby effectively improving the interface bonding strength of the composite material and reducing the internal pores.
[0012] Further preferably, the carbon material is a mixture of flake graphite and carbon nanotubes or a mixture of flake graphite and carbon nanofibers, and the mass ratio of flake graphite to carbon nanotubes or carbon nanofibers is 1:0.2-0.3.
[0013] Preferably, in step (3), the molding temperature is 180-230° C., the pressure is 5-20 MPa, and the time is 10-15 min.
[0014] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses green and natural polymer - lignin as raw material, and uses an alkaline-resistant surfactant as a structure-directing agent to carbonize lignin through a one-step hydrothermal method to obtain biomass porous carbon balls. During this reaction process, the surfactant molecules self-assemble in the aqueous solution. When the concentration of the surfactant aqueous solution reaches or exceeds the critical micelle concentration, spherical micelles are formed, inducing lignin to form spherical nanoparticles during the hydrothermal carbonization process. In a strong alkaline environment, functional groups in lignin, such as phenolic hydroxyl groups, will undergo a removal reaction. In addition, alkaline substances such as potassium hydroxide can be used as activators during the hydrothermal carbonization process to promote the formation of surface pore structures.
[0015] (2) The present invention uses airflow to mix fluorinated polymer powder, porous carbon balls and carbon materials. Based on the large specific surface area and rich pore structure of the porous carbon balls, the fluorinated polymer powder can be effectively adsorbed on the surface of the porous carbon balls, thereby improving the interface compatibility between the fluorinated polymer powder and the porous carbon balls, reducing the internal gaps / holes of the bipolar plate, and improving the mechanical strength of the bipolar plate. Compared with the prior art, the present invention has the characteristics of simple preparation process, short process and high efficiency.
[0016] (3) The present invention blends zero-dimensional porous carbon balls with one-dimensional and two-dimensional carbon materials such as flake graphite and carbon nanofibers to achieve synergistic effects and increase the conductive network inside the bipolar plate, thereby significantly improving the conductivity of the bipolar plate.
[0017] (4) The present invention provides a method for preparing a high-strength composite bipolar plate. Compared with the existing preparation method, the present invention does not require modification of the carbon material or polymer. The composite bipolar plate is prepared by a one-step hydrothermal method. The operation steps are simple, and the product has good electrical conductivity and mechanical strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The scanning electron microscope images of the porous carbon spheres prepared in step (1) of Example 1 of the present invention are shown in Figure 1. A is a scanning electron microscope image of the porous carbon spheres, and B is an enlarged scanning electron microscope image of the porous carbon spheres.
[0019] Figure 2 This is a scanning electron microscope image of the blend obtained in step (2) of Example 2 of the present invention. DETAILED DESCRIPTION
[0020] The present invention will be further described below with reference to the accompanying drawings and embodiments, but is not limited thereto.
[0021] Meanwhile, the experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are commercially available products unless otherwise specified. Example 1
[0022] (1) Weigh 6 g of lignin, 150 mL of 0.4% sodium dodecyl sulfate and 240 mL of 5% potassium hydroxide aqueous solution in a beaker, stir at 300 rpm for 30 min to obtain a mixed solution; pour the mixed solution into a hydrothermal reactor and react at 180 °C for 8 h. After the reactor is cooled to room temperature, filter the obtained suspension, wash the filtered solid matter with deionized water until the pH value is neutral, and dry at 80 °C to obtain porous carbon balls; (2) Weigh 4.8 g of polyvinylidene fluoride-hexafluoropropylene copolymer powder with a particle size of 5 nm, 1.8 g of porous carbon balls, 2.4 g of flake graphite and 0.6 g of carbon nanofibers, add them into a mixing pipe, mix the above substances with airflow, set the airflow pressure during feeding to 0.1 MPa, the airflow pressure during mixing to 0.7 MPa, and the mixing time to 40 s. Degas the mixed sample with a cyclone dust collector, set the airflow pressure to 0.1 MPa, and obtain a blend; (3) The blend is placed in a 0.3 mm thick molding mold and subjected to compression molding at 190°C and 20 MPa for 10 min. After compression molding, the bipolar plate is placed in a water cooling area and the mold is removed after 5 min of water cooling to obtain a high-strength composite bipolar plate.
[0023] Figure 1 The scanning electron microscope image of the porous carbon spheres prepared by the above method is shown in FIG. Figure 1 It can be seen that the porous carbon balls prepared by a one-step hydrothermal method using lignin as raw material have a size between 300 and 500 nm, are spherical as a whole, and have a relatively uniform size distribution. After magnification, it can be seen that there are rich mesoporous structures of 20 to 30 nm on the surface of the carbon balls. Therefore, in the process of mixing the fluorinated polymer powder through air flow, the large specific surface area and rich mesoporous structure of the porous carbon balls can achieve effective adsorption of the polymer resin powder. In the subsequent molding process, the molten polymer penetrates into the pores of the porous carbon balls, thereby reducing the interfacial pores between the carbon material and the polymer resin, enhancing its interfacial wetting properties with the porous carbon balls, and improving the interfacial bonding strength, thereby realizing the preparation of high-strength composite bipolar plates. Example 2
[0024] (1) Weigh 3 g of lignin, 45 mL of a 0.2% sodium sulfate aqueous solution of fatty alcohol polyoxyethylene ether, and 50 mL of a 6% potassium hydroxide aqueous solution in a beaker, and stir at 300 rpm for 20 min to obtain a mixed solution; pour the mixed solution into a hydrothermal reactor, react at 140 °C for 10 h, and after the reactor is cooled to room temperature, filter the obtained suspension, wash the filtered solid matter with deionized water until the pH value is neutral, and dry at 80 °C to obtain porous carbon balls; (2) Weigh 3.6 g of ethylene-tetrafluoroethylene copolymer powder with a particle size of 15 nm, 1.2 g of porous carbon balls, 1 g of flake graphite and 0.2 g of carbon nanotubes, add them into a mixing pipe, and mix the above substances using airflow. The airflow pressure during feeding is set to 0.1 MPa, the airflow pressure during mixing is set to 1 MPa, and the mixing time is 30 s; the mixed sample is degassed using a cyclone dust collector, and the airflow pressure is set to 0.2 MPa to obtain a blend; (3) The blend is placed in a 0.3 mm thick molding mold and subjected to compression molding at 230°C and 5 MPa for 10 min. After compression molding, the bipolar plate is placed in a water cooling area and the mold is removed after 5 min of water cooling to obtain a high-strength composite bipolar plate.
[0025] Figure 2 This is a scanning electron microscope image of the fluorine-containing polymer, porous carbon balls, flake graphite and carbon nanotubes mixed by air flow in Example 2. Figure 2 It can be seen that based on the rich pore structure on the surface of the porous carbon balls, after airflow mixing, due to the high polarity of the fluorinated polymer, the fluorinated polymer powder can form an effective coating on the surface of the porous carbon balls, reducing the pore structure between the porous carbon balls and the fluorinated polymer matrix, which is beneficial to improve the mechanical strength of the bipolar plate and realize the preparation of high-strength composite bipolar plates. At the same time, the carbon nanotubes are relatively evenly dispersed in the blend matrix, bridging with the porous carbon balls to form a rich network, and the flaky graphite is interspersed between the porous carbon balls and the carbon nanotubes, providing a rich contact surface, which greatly improves the conductivity of the bipolar plate. Example 3
[0026] (1) Weigh 5 g of lignin, 100 mL of 0.3% sodium secondary alkyl sulfonate and 200 mL of 5% sodium hydroxide aqueous solution in a beaker, stir at 300 rpm for 30 min to obtain a mixed solution; pour the mixed solution into a hydrothermal reactor, react at 160 ° C for 6 h, and after the reactor is cooled to room temperature, filter the obtained suspension, wash the filtered solid matter with deionized water until the pH value is neutral, and dry at 80 ° C to obtain porous carbon balls; (2) Weigh 13 g of polyvinylidene fluoride powder with a particle size of 2 μm, 2.6 g of porous carbon balls and 10.4 g of carbon nanofibers, add them into a mixing pipe, and mix the above substances using airflow. The airflow pressure during feeding is set to 0.2 MPa, the airflow pressure during mixing is set to 0.9 MPa, and the mixing time is 60 s; the mixed sample is degassed using a cyclone dust collector, and the airflow pressure is set to 0.1 MPa to obtain a blend; (3) The blend is placed in a 0.3 mm thick molding mold and subjected to compression molding at 190°C and 8 MPa for 15 min. After compression molding, the bipolar plate is placed in a water cooling area and the mold is removed after 5 min of water cooling to obtain a high-strength composite bipolar plate. Example 4
[0027] (1) Weigh 4 g of lignin, 120 mL of 0.2% sodium fatty alcohol polyoxyethylene ether sulfate and 100 mL of 6% potassium hydroxide aqueous solution in a beaker, stir at 300 rpm for 50 min to obtain a mixed solution; pour the mixed solution into a hydrothermal reactor, react at 160 ° C for 8 h, and after the reactor is cooled to room temperature, filter the obtained suspension, wash the filtered solid matter with deionized water until the pH value is neutral, and dry at 80 ° C to obtain porous carbon balls; (2) Weigh 8 g of polyvinylidene fluoride-hexafluoropropylene copolymer powder with a particle size of 500 nm, 2 g of porous carbon balls and 10 g of flake graphite, add them into a mixing pipe, and mix the above substances using airflow. The airflow pressure during feeding is set to 0.1 MPa, the airflow pressure during mixing is set to 0.8 MPa, and the mixing time is 45 s; the mixed sample is degassed using a cyclone dust collector, and the airflow pressure is set to 0.1 MPa to obtain a blend; (3) The blend is placed in a 0.3 mm thick molding mold and subjected to compression molding at 180°C and 15 MPa for 12 min. After compression molding, the bipolar plate is placed in a water cooling area and the mold is removed after 5 min of water cooling to obtain a high-strength composite bipolar plate. Example 5
[0028] (1) Weigh 9 g of lignin, 150 mL of 0.18% sodium secondary alkyl sulfate and 200 mL of 7% sodium hydroxide aqueous solution in a beaker, stir at 300 rpm for 40 min to obtain a mixed solution; pour the mixed solution into a hydrothermal reactor, react at 180 °C for 10 h, and after the reactor is cooled to room temperature, filter the obtained suspension, wash the filtered solid matter with deionized water until the pH value is neutral, and dry at 80 °C to obtain porous carbon balls; (2) Weigh 3 g of polyvinylidene fluoride powder with a particle size of 1 μm, 1.2 g of porous carbon balls, 1 g of flake graphite and 0.3 g of carbon nanofibers, add them into a mixing pipe, and mix the above substances using airflow. Set the airflow pressure during feeding to 0.1 MPa, the airflow pressure during mixing to 1 MPa, and the mixing time to 60 s; degas the mixed sample using a cyclone dust collector, set the airflow pressure to 0.0 MPa, and obtain a blend; (3) The blend is placed in a 0.3 mm thick molding mold and subjected to compression molding at 200°C and 10 MPa for 15 min. After compression molding, the bipolar plate is placed in a water cooling area and the mold is removed after 5 min of water cooling to obtain a high-strength composite bipolar plate. Comparative Example 1
[0029] (1) Weigh 4.8 g of polyvinylidene fluoride-hexafluoropropylene copolymer powder with a particle size of 5 nanometers, 1.8 g of graphite powder, 2.4 g of flake graphite and 0.6 g of carbon nanotubes, add them into a mixing pipe, mix the above substances with airflow, set the airflow pressure during feeding to 0.1 MPa, the airflow pressure during mixing to 0.7 MPa, and the mixing time to 40 s. Degas the mixed sample with a cyclone dust collector, set the airflow pressure to 0.1 MPa, and obtain a blend; (2) The blend is placed in a 0.3 mm thick molding mold and subjected to compression molding at 190°C and 20 MPa for 10 min. After compression molding, the bipolar plate is placed in a water cooling area and the mold is removed after 5 min of water cooling to obtain a composite bipolar plate. Comparative Example 2
[0030] (1) Weigh 6 g of lignin, 150 mL of 0.4% sodium dodecyl sulfate and 240 mL of 5% potassium hydroxide aqueous solution in a beaker, stir at 300 rpm for 30 min to obtain a mixed solution; pour the mixed solution into a hydrothermal reactor and react at 180 °C for 8 h. After the reactor is cooled to room temperature, filter the obtained suspension, wash the filtered solid matter with deionized water until the pH value is neutral, and dry at 80 °C to obtain porous carbon balls; (2) Weigh 4.8 g of polyethylene powder with a particle size of 5 nanometers, 1.8 g of porous carbon balls, 2.4 g of flake graphite and 0.6 g of carbon nanotubes, add them into a mixing pipe, and mix the above substances using airflow. Set the airflow pressure during feeding to 0.1 MPa, the airflow pressure during mixing to 0.7 MPa, and the mixing time to 40 s. Degas the mixed sample using a cyclone dust collector, set the airflow pressure to 0.1 MPa, and obtain a blend; (3) The blend is placed in a 0.3 mm thick molding mold and subjected to compression molding at 160°C and 20 MPa for 10 min. After compression molding, the bipolar plate is placed in a water cooling area and the mold is removed after 5 min of water cooling to obtain a composite bipolar plate. Comparative Example 3
[0031] (1) Weigh 6 g of lignin, 150 mL of 0.4% sodium dodecyl sulfate and 240 mL of 5% potassium hydroxide aqueous solution in a beaker, stir at 300 rpm for 30 min to obtain a mixed solution; pour the mixed solution into a hydrothermal reactor and react at 180 °C for 8 h. After the reactor is cooled to room temperature, filter the obtained suspension, wash the filtered solid matter with deionized water until the pH value is neutral, and dry at 80 °C to obtain porous carbon balls; (2) Weigh 24 g of polyvinylidene fluoride-hexafluoropropylene copolymer powder with a particle size of 5 nm, 9 g of porous carbon balls, 12 g of flake graphite and 3 g of carbon nanotubes, add the above substances into a torque rheometer, set the melt blending temperature to 200 ° C, the mixing speed to 60 rpm, and the mixing time to 10 min to obtain a blend; (3) The blend is placed in a 0.3 mm thick molding mold and subjected to compression molding at 190°C and 20 MPa for 10 min. After compression molding, the bipolar plate is placed in a water cooling area and the mold is removed after 5 min of water cooling to obtain a composite bipolar plate. Comparative Example 4
[0032] (1) Weigh 6 g of lignin, 150 mL of 0.4% sodium dodecyl sulfate and 240 mL of 5% potassium hydroxide aqueous solution in a beaker, stir at 300 rpm for 30 min to obtain a mixed solution; pour the mixed solution into a hydrothermal reactor and react at 180 °C for 8 h. After the reactor is cooled to room temperature, filter the obtained suspension, wash the filtered solid matter with deionized water until the pH value is neutral, and dry at 80 °C to obtain porous carbon balls; (2) Weigh 4.8 g of polyvinylidene fluoride-hexafluoropropylene copolymer powder with a particle size of 5 nm and 4.8 g of porous carbon balls, add them into a mixing pipe, and mix the above substances using airflow. The airflow pressure during feeding is set to 0.1 MPa, the airflow pressure during mixing is set to 0.7 MPa, and the mixing time is 40 s. The mixed sample is degassed using a cyclone dust collector, and the airflow pressure is set to 0.1 MPa to obtain a blend; (3) The blend is placed in a 0.3 mm thick molding mold and subjected to compression molding at 190°C and 20 MPa for 10 min. After compression molding, the bipolar plate is placed in a water cooling area and the mold is removed after 5 min of water cooling to obtain a composite bipolar plate.
[0033]
[0034] As shown in Table 1, the composite bipolar plates prepared in Examples 1 to 5 exhibit high electrical conductivity, excellent tensile strength and bending strength, with electrical conductivity of 92 to 133 S / cm, tensile strength of 30.2 to 36.8 MPa, and bending strength of 56.3 to 71.9 MPa. This is mainly due to the large specific surface area and rich mesoporous structure of the porous carbon balls. After airflow mixing, the fluoropolymer has a high polarity, which improves the affinity between the fluoropolymer and the carbon material, thereby achieving effective coating of the polymer on the surface of the porous carbon ball. During the molding process, the molten fluoropolymer is more likely to penetrate into the pores of the porous carbon ball, thereby reducing the pore structure between the porous carbon ball and the fluoropolymer matrix, which is beneficial to improving the mechanical strength of the bipolar plate and realizing the preparation of a high-strength composite bipolar plate. In addition, by blending zero-dimensional porous carbon balls with one-dimensional and two-dimensional carbon materials, carbon materials of multiple dimensions can synergize and build a rich conductive network, thereby greatly improving the conductivity of the bipolar plate.
[0035] When graphite powder is used instead of porous carbon balls, it can be seen from Comparative Example 1 that the tensile strength and bending strength of the bipolar plate are greatly reduced. This is because the graphite powder has less surface pore structure. During the blending process with the polymer, due to the poor interface compatibility between the two, continuous gaps or holes will appear at the interface during the blending process, resulting in the bipolar plate having poor mechanical strength and conductivity.
[0036] When the polymer matrix is changed to polyethylene, it can be seen from Comparative Example 2 that the conductivity, tensile strength and bending strength of the bipolar plate are greatly reduced. This is because polyethylene is a non-polar polymer and has a weak interaction with carbon materials. During the mixing process, carbon materials are prone to form agglomerates, which affects the conductivity and mechanical strength of the bipolar plate.
[0037] When the blending method is changed to melt blending, it can be seen from Comparative Example 3 that the conductivity, tensile strength and bending strength of the bipolar plate are all reduced. This is because in the molten state, the carbon material is easy to agglomerate, thereby forming large aggregates, which affects the formation of the conductive network inside the bipolar plate. In addition, in the molten state, higher temperatures and longer blending times will cause the polymer to age, which in turn leads to a decrease in the mechanical strength of the bipolar plate.
[0038] When the fluorine-containing polymer is blended with a single porous carbon ball, it can be seen from Comparative Example 4 that the bipolar plate exhibits a lower electrical conductivity. This is because the zero-dimensional porous carbon balls have limited contact points, making it difficult to form a continuous conductive path in the bipolar plate matrix, and a higher filling amount is required to reach the percolation threshold, resulting in a lower electrical conductivity of the composite material. At the same time, the zero-dimensional porous carbon balls have a small contact area with the polymer matrix, low stress transfer efficiency, and little effect on improving the mechanical strength of the bipolar plate. Therefore, the tensile strength and bending strength of the bipolar plate are slightly lower than those of the bipolar plate prepared by blending multi-dimensional carbon materials.
Claims
1. A method for preparing a high-strength composite bipolar plate, characterized in that: The steps include: (1) mixing lignin, a surfactant aqueous solution, and an alkaline aqueous solution, and subjecting the mixture to a hydrothermal treatment to obtain a suspension, and filtering, washing, and drying the suspension to obtain porous carbon balls; (2) placing the fluorine-containing polymer, porous carbon balls and carbon material in an air flow mixer and mixing them by air flow to obtain a blend; (3) The blend is compression molded to produce a high-strength composite bipolar plate.
2. The method for preparing a high-strength composite bipolar plate according to claim 1, characterized in that: In the step (1), the surfactant is one of sodium dodecyl sulfate, sodium fatty alcohol polyoxyethylene ether sulfate or sodium secondary alkyl sulfonate; the mass fraction of the surfactant aqueous solution is 0.18% to 0.4%; the alkaline aqueous solution is one of sodium hydroxide and potassium hydroxide aqueous solutions; the mass fraction of the alkaline aqueous solution is 5% to 7%; the mass ratio of the lignin, the surfactant and the alkaline compound in the alkaline aqueous solution is 1:0.03 to 0.1:1 to 2.
3. The method for preparing a high-strength composite bipolar plate according to claim 1, characterized in that: In the step (1), the hydrothermal treatment temperature is 140 to 180° C., and the hydrothermal treatment time is 6 to 10 hours.
4. The method for preparing a high-strength composite bipolar plate according to claim 1, characterized in that: In the step (2), the fluorine-containing polymer is one of ethylene-tetrafluoroethylene copolymer, polyvinylidene fluoride, or polyvinylidene fluoride-hexafluoropropylene copolymer; the particle size of the fluorine-containing polymer is 5 nanometers to 2 micrometers; the carbon material is one or a combination of flake graphite, carbon nanotubes, or carbon nanofibers; the mass ratio of the fluorine-containing polymer, porous carbon balls, and carbon material is 1:0.2-0.4:0.33-1.
25.
5. The method for preparing a high-strength composite bipolar plate according to claim 1, characterized in that: In the step (2), the air flow mixing pressure is 0.5 to 1 MPa, and the mixing time is 30 to 60 seconds.
6. The method for preparing a high-strength composite bipolar plate according to claim 4, characterized in that: The carbon material is a mixture of flake graphite and carbon nanotubes or a mixture of flake graphite and carbon nanofibers, and the mass ratio of flake graphite to carbon nanotubes or carbon nanofibers is 1:0.2-0.
3.
7. The method for preparing a high-strength composite bipolar plate according to claim 1, characterized in that: In the step (3), the molding temperature is 180-230° C., the pressure is 5-20 MPa, and the time is 10-15 min.
Citation Information
Patent Citations
Composite graphite bipolar plate for fuel cell and preparation method
CN114976086A
Composite bipolar plate, preparation method thereof and fuel cell
CN117325491A
Spherical carbon material and preparation method thereof
CN112794302A
High-conductivity bipolar plate as well as preparation method and application thereof
CN117254053A
Conductive polymer doped bipolar plate as well as preparation method and application thereof
CN117410512A
